Edukasi Fisioterapi Terhadap Keselamatan dan Kesehatan Kerja Pada Pengrajin Anyam Bambu di Desa Winong Trenggalek - Shofiana Wardani; Nurul Aini Rahmawati (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2024)
Bamboo crafts are works of art that have many benefits, such as musical instruments and household utensils. One way to make bamboo crafts is by weaving. The largest craft industry in the city of Trenggalek is the bamboo weaving industry. There are many health problems and work accidents in bamboo weavers such as complaints of low back pain, CTS or work accidents such as cuts, stabs, etc. The purpose of this physiotherapy education is to increase the understanding and knowledge of bamboo weaving craftsmen in order to avoid or resolve problems with the health and safety of workers. This activity shows results, namely that bamboo weaving craftsmen can understand the material well after being evaluated with a pre-test and post-test.